Islam and human rights - Mayer, Ann Elizabeth. (New Yok ; London)
xv, 299 sayfa
Keywords: “slam and Human Rights is a probing examination of how the Islamic tradition has been exploited for political ends by regimes and institutions seeking to legitimize policies inimical to human rights. Ann Elizabeth Mayer critically appraises Islamic human rights schemes that dilute the human rights afforded by international law, comparing them with the complex Islamic legal heritage and international human rights law. Challenging stereotypes about a supposedly monolithic Islam inherently incompatible with human rights, Mayer dissects the political motives behind the selective deployment of elements of the Islamic tradition by conservative forces seeking to delegitimize demands for democracy and human rights. The fifth edition provides an updated consideration of government policies on Islam and human rights activism and how they are affecting developments in several Middle Eastern countries, and features a new chapter on the resistance of human rights for sexual minorities by the Organization of Islamic Cooperation (OIC) project to co-opt international human rights law to criminalize 'defamation of Islam' occurring in the West. The new edition also analyzes the other most recent and important issues of the region, including: The burgeoning pressures in the Middle East for human rights leading up to the Arab Spring; The ambitious campaign of the (OIC) to influence the UN human rights system by forging alliances with non-Muslim states hostile to human rights; The concerted efforts by this cross-cultural alliance to subvert international human rights law under pretenses of supporting human rights; The intensifying controversies over issues of sexual orientation and gender identity in the Middle East; The Danish Cartoons controversy and the OIC project to co-opt international human rights law to criminalize 'defamation of Islam' occurring in the West“ --